IMPLIKASI RISET AKUNTANSI KEPERILAKUAN TERHADAP PENGEMBANGAN AKUNTANSI MANAJEMEN - ASRI DWIJA PUTRI, I G.A.M. (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 3 No 2 (2008))
This article discusses behavioral accounting related to area of management accounting. The discussion begins with behavioral accounting and its development, management accounting, behavioral accounting research in management accounting, followed by an explanation of some management accounting techniques, including budgeting, balanced scorecard, just in time, and total quality management. The final part is about the implication of accounting behavioral research on management accounting.
Keywords: behavioral accounting, management accounting, budgeting, balanced scorecard, just in time, total quality management